2021
DOI: 10.1177/23259671211038397
|View full text |Cite
|
Sign up to set email alerts
|

The Danger Zone for Iatrogenic Neurovascular Injury in All-Inside Lateral Meniscal Repair in Relation to the Popliteal Tendon: An MRI Study

Abstract: Background: Lateral meniscal repair can endanger the nearby neurovascular structure (peroneal nerve or popliteal artery). To our knowledge, there have been no studies to evaluate the danger zone of all-inside meniscal repair through the anteromedial (AM) and anterolateral (AL) portals in relation to the medial and lateral edges of the popliteal tendon (PT). Purpose: To establish the risk of neurovascular injury and the danger zone in repairing the lateral meniscus in relation to the medial and lateral edges of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The weakness of this cadaveric study was that it did not evaluate the distances with the knee in the figure-of-4 position with appropriate varus force, which is the actual arthroscopic situation for lateral meniscal repair. The previous MRI study 5 evaluated the risk of iatrogenic peroneal nerve injury related to the medial and lateral borders of the PT with the knee in a slightly flexed position and found a risk of iatrogenic peroneal nerve injury in repairing the lateral meniscal tissue through both the anteromedial and the anterolateral portals related to both the medial and the lateral borders of the PT. They found that repairing the lateral meniscal tissue in relation to the medial border of the PT through the anterolateral portal was safer than through the anteromedial portal; however, the anterolateral portal was more dangerous than the anteromedial portal in repairing the lateral meniscal tissue in relation to the lateral border of the PT.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The weakness of this cadaveric study was that it did not evaluate the distances with the knee in the figure-of-4 position with appropriate varus force, which is the actual arthroscopic situation for lateral meniscal repair. The previous MRI study 5 evaluated the risk of iatrogenic peroneal nerve injury related to the medial and lateral borders of the PT with the knee in a slightly flexed position and found a risk of iatrogenic peroneal nerve injury in repairing the lateral meniscal tissue through both the anteromedial and the anterolateral portals related to both the medial and the lateral borders of the PT. They found that repairing the lateral meniscal tissue in relation to the medial border of the PT through the anterolateral portal was safer than through the anteromedial portal; however, the anterolateral portal was more dangerous than the anteromedial portal in repairing the lateral meniscal tissue in relation to the lateral border of the PT.…”
Section: Discussionmentioning
confidence: 99%
“…An all–inside meniscal repair device can endanger the peroneal nerve when the repair involves damage close to the medial and/or lateral borders of the PT and the tear type warrants meniscocapsular repair because the peroneal nerve is located at the posterolateral aspect of the knee joint. There have been several cadaveric and MRI-based studies that evaluated the risk of iatrogenic peroneal nerve injury during lateral meniscal repair 2,5,6,12,13,18,21 ; however, the results of these studies may not have accurately represented the true operative situation. The cadaveric studies may have been inaccurate because they all used midleg to midthigh cadaveric sections, which would have less than normal muscle and neurovascular tensions, and also were not evaluated in the actual surgical figure-of-4 arthroscopic position.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations